Fine-tuning the fruit-tracking hypothesis: Spatiotemporal links between fruit availability and fruit consumption by birds in Andean mountain forests - Blendinger, Pedro Gerardo (2012)
1. The fruit-tracking hypothesis predicts spatiotemporal links between changes in the abundance of fruit-eating birds and the abundance of their fleshy-fruit resources. 2. While the spatial scale of plant-frugivore interactions has been explored to understand mismatches between observed and expected fruit-frugivore patterns, methodological issues such as the consequences of measuring fruit and frugivore abundance rather than fruit availability and fruit consumption have not been evaluated. 3. Here, we explored whether predicted fruit-frugivore spatiotemporal links can be captured with higher accuracy by proximate measurements of interaction strength. We used a 6-ha grided plot in an Andean subtropical forest to study the link between (i) fruit and fruit-eating bird abundances; (ii) fruit availability and frequency of fruit consumption; and (iii) covariation between frugivore abundance and frequency of frugivory. We evaluated these links for the entire frugivore assemblage and for the four most important species using data gathered bimonthly along a 2-year period. 4. Fleshy-fruit availability and abundance varied sharply temporally and were patchily distributed in mosaics that differed in fruit quantity. Fruit availability and abundance also varied along spatial gradients extended over the whole study plot. We found a strong response of the entire frugivorous bird assemblage to fruit availability over time, and a weakly significant relationship over space at the local scale. The main frugivore species widely differed in their responses to changes in fruit abundance in such a way that response at the assemblage level cannot be seen as the sum of individual responses of each species. Our results suggest that fruit tracking in frugivorous-insectivorous birds may be largely explained by species-specific responses to changes in the availability of fruits and alternative resources. 5. In agreement with our prediction, more accurate measurements of interaction strength described fruit-frugivore relationships better than traditional measurements. Moreover, we show that covariation between frugivore abundance, frequency of fruit consumption and fruit availability must be included in the fruit-tracking hypothesis framework to demonstrate (or reject) spatiotemporal fruit tracking. We propose that estimation of nutrient and energy availability in fruits could be a new frontier to understanding the forces driving foraging decisions that lead to fruit tracking. © 2012 British Ecological Society.